BIOSECURITY AND ZOONOTIC DISEASE RISK AT LIVESTOCK EXHIBITION EVENTS - Larson, Diane (My University, 2017)
One of the missions of the Kansas Department of Agriculture Division of Animal Heath is to ensure the public health, safety, and welfare of Kansas' citizens through prevention, control, and eradication of infectious and contagious diseases and conditions affecting the health of livestock and domestic animals in the state of Kansas. This mission directly applies to animal exhibition events in Kansas. These types of events pose health risks to both humans and animals that attend the event. Exhibition animals are at an increased risk of contracting an infectious disease due to the commingling of animals from multiple geographical locations. Exhibitors can reduce this risk by taking biosecurity measures with their exhibitions animals before, during, and after exhibition events. People visiting these events are at an increased risk of contracting zoonotic diseases due to their contact with animals and their environments. The main objectives of this field experience were to describe the extent of the zoonotic disease risk at the Kansas State Fair through an observational study, and to understand the biosecurity knowledge and practices of youth animal exhibitors in Kansas by conducting a survey of Kansas 4-H animal exhibitors. The results of the observational study at the Kansas State Fair demonstrate the significant amount of zoonotic disease risk present on the fairgrounds. These results were used to provide the Kansas State Fair administration with zoonotic disease risk mitigation strategies for the event. The results from the Kansas 4-H biosecurity survey exposed gaps in the biosecurity knowledge and practices of youth exhibitors. This information was used to provide recommendations to the Kansas State Research and Extension 4-H office for future education and outreach efforts with their youth exhibitors.
Keywords: Animal Contact; Biosecurity; Hand Hygiene; Livestock Exhibitions; Risk Behavior; Zoonoses